Effect of a Reduction in Uric Acid on Renal Outcomes During Losartan Treatment: A Post Hoc Analysis of the Reduction of Endpoints in Non-Insulin-Dependent Diabetes Mellitus With the Angiotensin II Antagonist Losartan Trial - Miao, Yan; Ottenbros, Stefan A.; Laverman, Goos D.; Brenner, Barry M.; Cooper, Mark E.; Parving, Hans-Henrik; Grobbee, Diederick E.; Shahinfar, Shahnaz; de Zeeuw, Dick; Lambers Heerspink, Hiddo J. (Hypertension (Dallas, Tex. 1979), 2011)
Emerging data show that increased serum uric acid (SUA) concentration is an independent risk factor for end-stage renal disease. Treatment with the antihypertensive drug losartan lowers SUA. Whether reductions in SUA during losartan therapy are associated with renoprotection is unclear. We therefore tested this hypothesis. In a post hoc analysis of 1342 patients with type 2 diabetes mellitus and nephropathy participating in the Reduction of Endpoints in Non-Insulin-Dependent Diabetes Mellitus With the Angiotensin II Antagonist Losartan Trial, we determined the relationship between month 6 change in SUA and renal endpoints, defined as a doubling of serum creatinine or end-stage renal disease. Baseline SUA was 6.7 mg/dL in placebo and losartan-treated subjects. During the first 6 months, losartan lowered SUA by −0.16 mg/dL (95% CI−0.30 to −0.01; P=0.031) as compared with placebo. The risk of renal events was decreased by 6% (95% CI10% to 3%) per 0.5-mg/dL decrement in SUA during the first 6 months. This effect was independent of other risk markers, including estimate glomerular filtration rate and albuminuria. Adjustment of the overall treatment effects for SUA attenuated losartanʼs renoprotective effect from 22% (95% CI6% to 35%) to 17% (95% CI1% to 31%), suggesting that approximately one fifth of losartanʼs renoprotective effect could be attributed to its effect on SUA. Losartan lowers SUA levels compared with placebo treatment in patients with type 2 diabetes mellitus and nephropathy. The degree of reduction in SUA is subsequently associated with the degree in long-term renal risk reduction and explains part of losartanʼs renoprotective effect. These findings support the view that SUA may be a modifiable risk factor for renal disease.